2004
DOI: 10.1080/03655230410018354
|View full text |Cite
|
Sign up to set email alerts
|

Concurrent Chemoradiotherapy with Pirarubicin and 5-fluorouracil for Resectable Oral and Maxillary Carcinoma

Abstract: This concurrent chemoradiotherapy is very useful for oral and maxillary carcinoma as a preoperative modality with remarkably high response rate and acceptable adverse events.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Many studies have demonstrated that combined chemotherapy and radiation is a highly effective treatment modality for increasing the survival of patients with advanced disease [2,3,9-11]. Concurrent chemoradiotherapy has been established as an appropriate standard for many patients with locally advanced head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Many studies have demonstrated that combined chemotherapy and radiation is a highly effective treatment modality for increasing the survival of patients with advanced disease [2,3,9-11]. Concurrent chemoradiotherapy has been established as an appropriate standard for many patients with locally advanced head and neck cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Tsukuda et al reported that the complete response rate were 93% in stage III and 54% in stage IV, by treating head and neck cancer with S-1 and radiotherapy at a total dose of 66-70.2 Gy [14]. There have been few reports on the effect of preoperative chemoradiotherapy with a total radiation dose of 40-Gy [2,3]. …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mücke et al also demonstrated the efficacy of low-dose radiotherapy (total dose, 20 Gy) combined with concurrent low-dose cisplatin (12.5 mg/m 2 ) for 5 days, as pre-operative therapy (24). However, Iguchi et al reported the use of combined intra-arterial pirarubicin and continuous intravenous 5-fluorouracil (5-FU) with a radiation dose of 40 Gy (25). This study concluded that these regimens were effective as a pre-operative treatment, with a notably high response rate and an acceptable incidence of adverse events.…”
Section: Histopathological Response N ------------------------------mentioning
confidence: 99%
“…However, postoperative dysfunction such as disturbances of speech, swallowing, mastication and esthetics can affect quality of life in advanced cases [2] , [8] . Studies employing adjuvant RT or chemoradiotherapy (CRT) after surgery outnumber studies of preoperative concepts, although preoperative therapy concepts have achieved good loco-regional control and a good survival rate as the standard approach in some institutions and have been rated positively in analytical reports [5] , [6] , [7] , [9] , [10] . Therefore, in recent decades, concurrent CRT for advanced oral SCC has been used to enable minimally invasive surgery or organ preservation [3] , [4] , [8] , [9] , [11] .…”
Section: Introductionmentioning
confidence: 99%